2011
DOI: 10.1016/j.molcel.2010.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Robust Control of Nitrogen Assimilation by a Bifunctional Enzyme in E. coli

Abstract: Bacteria regulate the assimilation of multiple nutrients to enable growth. How is balanced utilization achieved, despite fluctuations in the concentrations of the enzymes that make up the regulatory circuitry? Here we address this question by studying the nitrogen system of E. coli. A mechanism based on the avidity of a bifunctional enzyme, adenylyltransferase (AT/AR), to its multimeric substrate, glutamine synthetase, is proposed to maintain a robust ratio between two key metabolites, glutamine and α-ketoglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 47 publications
2
55
0
Order By: Relevance
“…In this way, the activity of the two domains would have less steric hindrance from each other, and the two opposed activities would not interfere with each other. However, an opposing view on the interactions between ATase and GS has also been presented, which was not based on structural but on biochemical data; here it was suggested that the binding of one ATase domain to a GS monomer has a strong cooperative effect on the binding of the other domain to an adjacent GS monomer (107). In contrast to the above-mentioned model, the two domains of the same ATase would both point toward GS.…”
Section: Adenylyltransferase/adenylyl-removing Enzymementioning
confidence: 87%
See 2 more Smart Citations
“…In this way, the activity of the two domains would have less steric hindrance from each other, and the two opposed activities would not interfere with each other. However, an opposing view on the interactions between ATase and GS has also been presented, which was not based on structural but on biochemical data; here it was suggested that the binding of one ATase domain to a GS monomer has a strong cooperative effect on the binding of the other domain to an adjacent GS monomer (107). In contrast to the above-mentioned model, the two domains of the same ATase would both point toward GS.…”
Section: Adenylyltransferase/adenylyl-removing Enzymementioning
confidence: 87%
“…It should be noted that data from some articles (107,572,573) are based on the assumption that the 2-oxoglutarate-over-glutamine ratio would be maintained homeostatically, which, in our opinion, might not be valid under all conditions (see below). The ratio was found to be constant at 1.8 for cells growing in chemostat cultures under conditions of glucose limitation and excess ammonium but only at relatively high specific growth rates (Ͼ0.4 h Ϫ1 ).…”
Section: Measuring Metabolites In Vivomentioning
confidence: 95%
See 1 more Smart Citation
“…This robustness manifests itself, for example, in bacteria, which are extremely flexible and capable of maintaining functions essential for survival under a wide variety of conditions [100]. Signaling pathways take over a key role in these adaptation processes in all kinds of cells, and show amazingly reliable functioning [101][102][103][104].…”
Section: Functional Robustnessmentioning
confidence: 99%
“…Such mutants grow normally in steady glucose but are strikingly deficient in an oscillating glucose environment (Xu et al, 2012a;Xu et al, 2012b). Related work investigates additional nutrients and stresses, and the robustness of biological responses to them (Goodarzi et al, 2010;Hart et al, 2011;Peterson et al, 2012;Reaves and Rabinowitz, 2011a, b).…”
Section: Aims Summary Aim 1: Reveal the Interplay Between Different Nmentioning
confidence: 99%